'Dirt, Death and Danger? I Don't Recall Any Adverse Reaction …': Masculinity and the Taint Management of Hospital Private Security Work. Issue 6 (9th July 2014) - Johnston, Matthew S.; Hodge, Edwin
<x xml:space="preserve">Abstract</x> Drawing on an ethnographic narrative written by one of the authors following his resignation from a hospital private security team in Ottawa, Canada and interview data gleaned from eight security men (all former colleagues), this article explores how hospital private security officers draw on discourses of masculinity to navigate the 'dirty' boundaries of their work, and to preserve their alpha‐guard statuses as controlled, autonomous and authoritative subjects. We found that hospital guards manage and deflect taint status by emphasizing their resiliency, emotional detachment and enthusiasm towards morbid, disturbing and dangerous tasks. Guards who seek to challenge these components of the job may be subject to gender harassment and reprisal from other guards, senior security officials and nursing staff. Overall, these narratives call attention to the necessity of hospital training programmes, de‐briefing exercises and best‐communication practices that promote the physical and emotional well‐being of persons who engage in intensive forms of dirty work.